PENGARUH DISMENORE TERHADAP AKTIVITAS BELAJAR MAHASISWI DI PROGRAM STUDI DIII KEBIDANAN - Hironima Niyati Fitri (STIKes CHMK, 2020)
Menstrual disorders are conditions when the menstrual cycle experiences anomalies or abnormalities. Dysmenorrhea is one of the menstrual abnormalities and is a medical condition that occurs during menstruation / menstruation which can interfere with activities and require treatment that is characterized by pain or pain in the abdomen or pelvis. Dysmenorrhoea occurs in 30-75% of women and requires treatment. Preliminary surveys conducted showed that female students who experience menstrual pain (dysmenorrhea) felt out of concentration and were not eager to participate in learning activities due to the pain caused. This study aims to analyze the effect of dysmenorrhea on student learning activities in the Midwifery Diploma Program. This research is a descriptive study with cross sectional method. This research was conducted from January to February 2020. Data were collected with the help of a questionnaire. The number of samples in this study was a total sampling of 118 people. Data analysis using the Spearman rank correlation test. The results showed that there was a significant relationship between dysmenorrhea with learning activities (0,000. <0.05) The conclusion of this study was that there was an influence of dysmenorrhea with learning activities on Midwifery DIII students